Aplikasi Mendeteksi Probiotik Dari Bakteri Asam Laktat Pada Pliek U Menggunakan Tsukamoto - Bimesifa Prima Septi (STMIK Budi Darma, 2019)
In the process of making Pliek U, there must be a maker who does not make Pliek U with the right time so that the nutritional content of Pliek U becomes unhealthy, that is containing bad bacteria. make Pliek U containing Lactic Acid Bacteria that have the potential as Probiotics. This study uses the Tsukamoto method with the rule IF ... THEN, in the process of knowing probiotics by inputting the process of making Pliek U so that the application will produce the Lactic Acid Bacteria contained in Pliek U as Probiotics or Not. The purpose of making this application is to be able to help fans or makers of Pliek U find out the types of healthy bacteria produced by Pliek U and after Pliek U research is safe to consume if the time of crushing and fermentation time is right.